Effect of Industrial Soil Contamination and Fertilizer Management on Growth, Yield and Metal Uptake by BARI Tomato 8 - Shamsuzzoha, M; Khan, M A (Journal of the Bangladesh Agricultural University, 2024)
The concern about industrial pollution and food safety is growing due to crop contamination and a major route to human exposure. The experiment was completed at a net house of Sher-e-Bangla Agricultural University during November 2021 to April 2022 to find out the effect of industrial soil pollution and fertilizer management on growth, yield and metal accumulation by BARI Tomato 8. Industrially polluted soils were collected from contaminated areas considering the soil pollution intensity. The physico-chemical properties were determined in soils. The experiment consists of two-factor, as Factor A: Six different soils (S0: Non-polluted soil; S1: Polluted soil-1, S2: Polluted soil-2; S3: Polluted soil-3, S4: Polluted soil-4 and S5: Polluted soil-5) and Factor B: Three fertilizer treatments (T0: Control; T1: 100% soil test basis dose of fertilizer; T2: 50% soil test basis dose of fertilizer and 50% nutrient from cowdung). High yielding tomato variety BARI Tomato 8 was used for experiment. Among the soils, the highest tomato yield was found in S1 and S5 polluted soils, while the lowest was obtained in S4 and S0 soils. The highest tomato yield was recorded in T2 treatment and the lowest in T0 treatment. The highest tomato fruit dry matter, Pb (1.359 mg kg-1) and Cd (0.759 mg kg-1) concentrations were found in T0 treatment and the lower levels were obtained in T1 (100% RDCF) and T2 (100% RDCF + 50% nutrient from cowdung) treatments. The higher tomato Pb and Cd concentrations were recorded in polluted soils with T0 and T1 treatments and the lower with T2. The highest tomato Pb concentration (1.656 mg kg-1) was obtained in S4T1 and the lowest (0.501 mg kg-1) in S3T2. The highest tomato Cd concentration (1.149 mg kg-1) was obtained in S5T0 and the lowest (0.097 mg kg-1) in S2T2 treatment combinations. J Bangladesh Agril Univ 22(4): 404–411, 2024